THE EVOLUTION OF SEMANTIC FIELDS IN HISTORICAL LINGUISTICS: A COMPARATIVE STUDY OF ENGLISH AND UZBEK (Scientific journal of the Fergana State University, 2025)
This article examines the evolution of semantic fields in historical linguistics through a comparative analysis of English and Uzbek. The study explores how socio-political, cultural, and technological changes have influenced the transformation of meaning in both languages. By employing diachronic and synchronic methods, it tracks shifts in core semantic fields such as governance, technology, and trade across different historical periods. English, shaped by the Norman Conquest and colonial expansion, and Uzbek, influenced by Persian, Arabic, and Russian linguistic contact, demonstrate both shared and divergent semantic evolutions. English has experienced gradual semantic shifts, while Uzbek underwent more abrupt changes, particularly during the Soviet era. The findings highlight patterns of semantic broadening, metaphorization, and borrowing, offering insights into the dynamic relationship between language, culture, and history. This research contributes to the broader field of historical linguistics by identifying universal trends and language-specific adaptations in semantic evolution.